Effect of Host Species on Hatchability of Fasciola hepatica and Fasciola gigantica Eggs from Sheep and Cattle - Sara Larki; Mohammad hosein Razi jalali; Saeed Goodarzi; Mina Zamani (Pasteur Institute of Iran, 2020)
Introduction: Successful development of free-living stages of parasitic helminths depends on larva ability to survive, develop, and hatch. In this study, we aimed to study the host role in the hatching process of Fasciola species. Methods:  Fasciola hepatica and Fasciola gigantica eggs were collected from adult worms that originated from naturally infected sheep and cattle livers and were incubated at 26±1°C for 15 days. The percentage of hatched and developed eggs were obtained for each isolate under a light microscope. A polymerase chain reaction followed by restriction fragment length polymorphism (PCR-RFLP) was applied to identify the F. hepatica and F. gigantica species. Results: Our findings showed no significant differences in the development rates of F. gigantica and F. hepatica eggs in sheep (69.32% and 72.71%) and cattle (73.56% and74.69%). However, the rates of hatched eggs of F. gigantica and F. hepatica originated from cattle (69.19% and 62.36%) were almost twice the rates in sheep (31.69% and 32.59%), indicating a significant difference. Conclusion: This study demonstrated that host species significantly affect the hatching of Fasciola eggs as the hatching rates of F. gigantica and F. hepatica originated from cattle were higher than those taken from sheep did not affect their larval development. Thus, in addition to environmental factors, the hatching phenomenon is influenced by host species.